Hallsta Pappersbruks virkesförsörjning - Dietrichson, Johan; Jensen, Christian (2010)
Competition of spruce fiber raw materials has increased dramatically in the last few years, leading to the fact that transportation costs in the current situation represents a much larger share of the total raw material cost. The Holmen-owned pulp industry Hallsta Paper Mill's location on the coast also constitutes a problem, because of the lack of raw material, which is much larger there, than for a pulp mill located in the hinterland. For a coastal industry it’s therefore natural to import much of the raw material by boat or to buy it from the timber terminals, in order to maintain good profitability. The purpose of this study was to analyze how the size of Hallsta Paper Mill timber supply area, without competition, with competition and with terminal use, affects the company ́s transport costs. The data in the analysis consisted of kNN-Sweden, produced at SLU in 2001, which was dealt in the computer software ESRI ArcGIS 9.3. The results showed that the current competitive situation, results in an increase of Hallsta’s medium transport distances from the forest to the industry with 52 km, compared with an uncompetitive market. In terms of transport costs for a truck, this represents an increase of 30 kr/m3fub by additional costs. Transport costs represent here approximately 23% of the total costs of wood procurement. The study also showed that Hallsta’s use of their existing timber terminals in the north, reduces their total cost of wood supply significantly. This reduces the total costs about 4 %, corresponding 16 MSEK, when 30 % of Hallsta’s annual wood supply is purchased from the terminals.